FAKTOR YANG BERHUBUNGAN DENGAN STUNTING PADA BALITA - Satria Dewi, Hellen; Kawuryan, Uji; Pratama, Kharisma (Literasi Intelektual, 2024)
Background: Adequate and good-quality nutritional intake is essential for toddlers. When nutritional needs are not met, toddlers’ physical and intellectual growth can be impaired. One of the most common nutritional problems in toddlers is stunting. In 2022, the incidence of stunting at Lumar Health Center was 19%, ranking tenth in Bengkayang Regency. Among five villages in the area, three had the highest rates of stunting in Lumar District.Objective: This study aimed to analyze the factors associated with the incidence of stunting among toddlers in the working area of the Lumar Health Center.Methods: This research used a cross-sectional design with a population of 102 respondents and a sample of 51 respondents selected using a random sampling technique.Results: Most toddlers had short stature 38 (74.5%), normal birth weight 41 (80.4%), a history of exclusive breastfeeding 28 (54.9%), families with low economic status 43 (84.3%), good nutritional knowledge 40 (78.4%), and appropriate feeding patterns 32 (62.7%). The chi-square test showed that birth weight (p = 0.000) and history of exclusive breastfeeding (p = 0.019) were significantly associated with stunting incidence, while economic status (p = 0.634), nutritional knowledge (p = 0.428), and feeding patterns (p = 0.100) were not.Conclusion: Birth weight and a history of exclusive breastfeeding are factors significantly associated with the incidence of stunting among toddlers in the Lumar Health Center working area.